2019
DOI: 10.1111/jpi.12579
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin differentially regulates pathological and physiological cardiac hypertrophy: Crucial role of circadian nuclear receptor RORα signaling

Abstract: Exercise-induced physiological hypertrophy provides protection against cardiovascular disease, whereas disease-induced pathological hypertrophy leads to heart failure. Emerging evidence suggests pleiotropic roles of melatonin in cardiac disease; however, the effects of melatonin on physiological vs pathological cardiac hypertrophy remain unknown. Using swimming-induced physiological hypertrophy and pressure overload-induced pathological hypertrophy models, we found that melatonin treatment significantly improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 56 publications
(95 reference statements)
2
36
0
Order By: Relevance
“…Cardiac hypertrophy is an important characteristic of many cardiovascular diseases; it usually results in heart failure and is a major cause of mortality worldwide [1]. Cardiac hypertrophy results in myocardial adverse remodeling, which includes myocardial fibrosis, cardiomyocyte death, and cardiac dysfunction [2][3][4]. Although remarkable efforts have been made by researchers to unveil the molecular pathophysiology and develop effective methods to prevent or reverse cardiac hypertrophy, to date there has no satisfactory clinical therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac hypertrophy is an important characteristic of many cardiovascular diseases; it usually results in heart failure and is a major cause of mortality worldwide [1]. Cardiac hypertrophy results in myocardial adverse remodeling, which includes myocardial fibrosis, cardiomyocyte death, and cardiac dysfunction [2][3][4]. Although remarkable efforts have been made by researchers to unveil the molecular pathophysiology and develop effective methods to prevent or reverse cardiac hypertrophy, to date there has no satisfactory clinical therapy.…”
Section: Introductionmentioning
confidence: 99%
“…From the survival analysis, our results were consistent with previous studies. Actually, the etiology of AMI was complicated, included alternated lipid metabolism, inflammatory reaction, oxidation injury, and other pathological processes [29][30][31][32]. Herein, we hypothesized that the NHR, a novel index composed of inflammatory cell and lipid cholesterol, might reflect the inflammatory status and the lipid metabolism more comprehensively.…”
Section: Discussionmentioning
confidence: 99%
“…Bro-Jeppesen et al reported baseline plasma IL-6 and IL-10 levels were significantly higher in non-survivors compared with survivors [11,12]. Melatonin, an anti-oxidant and anti-inflammatory agent, improves neurological outcomes and preserves hippocampal mitochondrial function in cardiac arrest [36], which may be associated with its protection against inflammation [22,[37][38][39], myocardial ischemia-reperfusion injury [40][41][42][43], ventricular fibrillation [44], cardiac hypertrophy [45], dilated cardiomyopathy [46], and mitochondria-related disorders [47,48]. As neutralization of IL-17 rescues neuroinflammation [49], melatonin may contribute to the complex role of IL-17 signaling in ROSC [50].…”
Section: Discussionmentioning
confidence: 99%